Use some plant extracts in control the Varroa destructor (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Field studies were conducted in the Department of Biological Control Techniques / Technical College of Al-Mussaib during the Period 2016-2017, Using  different concentration of extracts for Allium stivum and Coriandrum sativum  to control the  Varroa destructor as well as a survey of Varroa destructor in different areas of Babylon province .      The results showed that Varroa destructor was found in high density and different frequency in areas  reached to  89% in Alkawther and less infection 32% is Alnile.the extract of Coriandrum sativum  high  signification rate for killing 75.33% at 100%  conc. While the lest rate 12.11 at 25% conc. The result showed  that  Alliwm sativum has high rate  in killing rate reached  to  83%  at 100% conc. while the killing rate reached at  34.3 at 25% concentration .